Community’s Willingness to Pay for Improving Public Healthcare Services: A Contingent Valuation Study in the Coastal Hazard-prone Areas of Bangladesh (The Dhaka University Journal of Earth and Environmental Sciences, 2025)
Health service improvement in the coastal remote areas of Bangladesh is very essential to tackle the adverse effects on community health caused by frequent natural hazards. This research was conducted to explore the coastal community’s concerns about upgrading public healthcare facilities and determine their willingness to pay (WTP) for improving services at the Upazila Health Complex of Shyamnagar upazila of Satkhira, Bangladesh through the contingent valuation method (CVM). A binary logistic regression model was applied to find out factors influencing the variation in willingness to pay and the mean willingness to pay for healthcare improvement was estimated to be approximately Tk 60 using a probit model. The findings suggest that if the government can build public trust by ensuring the presence of qualified doctors and staff, adequate medical supplies, upgraded water, sanitation, and hygiene (WASH) facilities, and the provision of specialized diagnostic equipment such as X-ray machines and laboratory testing tools in the Upazila Health Complex, significant public support can be mobilized to raise funds for these improvements. The research outcome would help adopt appropriate health financing policies for improving the service quality and developing the overall facilities of public health institutions.The Dhaka University Journal of Earth and Environmental Sciences, Vol. 14(1), 2025, P 49-63